(untitled) (Dermatology Reports, 2025)
Dear Editor, Increased prevalence of cancer, in particular lymphomas, has been observed in patients with multiple sclerosis (MS) treated with fingolimod. We report the first case of primary cutaneous marginal zone lymphoma (PCMZL) that developed under long-term fingolimod therapy for MS. [...]